The effectiveness of forward guidance in an estimated DSGE model for the Euro area: The role of expectations - Roberta Cardani; Alessia Paccagnini; Stelios Bekiros (University College Dublin, UCD School of Economics, 2016)
We assess the effectiveness of the forward guidance undertaken by European Central Bank using a standard medium-scale DSGE model à la Smets and Wouters (2007). Exploiting data on expectations from surveys, we show that incorporating expectations should be crucial in performance evaluation of models for the forward guidance. We conduct an exhaustive empirical exercise to compare the pseudo out-of-sample predictive performance of the estimated DSGE model with a Bayesian VAR and a DSGE-VAR models. DSGE model with expectations outperforms others for inflation; while for output and short term-interest rate the DSGE-VAR with expectations reports the best prediction.
Keywords: C52; C53; E58; E52; 330; DSGE Bayesian estimation; Survey Professional Forecasts; Real Time data